Contemporary Irish Women Poets : Memory and Estrangement. - Collins, Lucy. (Liverpool : Liverpool University Press, 2015)
Original study of contemporary women poets in Ireland, presenting readings of four important poets (Eavan Boland, Eiléan Ní Chuilleanáin, Mairéad Byrne and Vona Groarke) and exploring themes and patterns in contemporary Irish women's poetry.
Cover -- Contents -- Acknowledgements -- Abbreviations -- Introduction: Memory, Estrangement and the Poetic Text -- I Concepts -- 1 Lost Lands: The Creation of Memory in the Poetry of Eavan Boland -- 2 Between Here and There: Migrant Identities and the Contemporary Irish Woman Poet -- 3 Private Memory and the Construction of Subjectivity in Contemporary Irish Women's Poetry -- II Achievements -- 4 Eiléan Ní Chuilleanáin's Spaces of Memory -- 5 Medbh McGuckian's Radical Temporalities -- 6 Catherine Walsh: A Poetics of Flux -- 7 Vona Groarke: Memory and Materiality -- Conclusion: Memories of the Future -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books